2007
DOI: 10.4152/pea.200704391
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Nickel Alloy Electrodeposition – Influence of Triethanolamine

Abstract: Compared to pure zinc plating, zinc alloys provide several advantages. A zinc alloy generally offers superior sacrificial protection to steel since it corrodes more slowly than pure zinc. A search for a non-cyanide zinc plating bath resulted on the development of a zinc nickel sulphamate bath. To obtain better quality zinc-nickel deposits, triethanolamine was added to the bath. In this paper the influence of triethanolamine in zinc-nickel plating from sulphamate bath has been investigated through current effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
0
7
0
5
Order By: Relevance
“…These in turn depend on bath composition, additives, current density, temperature and thickness of electrodepostion (Ravindran and Muralidharan 2007;Rizwan et al 2007;Shivakumara et al 2007;Rahman et al 2009). Chitharanjan reported the increase of nickel content, corrosion resistance and Vickers microhardness of the deposit with applied current density up to 3 A dm -2 .…”
Section: Introductionmentioning
confidence: 98%
“…These in turn depend on bath composition, additives, current density, temperature and thickness of electrodepostion (Ravindran and Muralidharan 2007;Rizwan et al 2007;Shivakumara et al 2007;Rahman et al 2009). Chitharanjan reported the increase of nickel content, corrosion resistance and Vickers microhardness of the deposit with applied current density up to 3 A dm -2 .…”
Section: Introductionmentioning
confidence: 98%
“…http TEA has been used as a complexing agent to obtain alloys such as Zn-Ni. In these cases it has improved the current efficiency and has been added onto the cathode surface to promote uniform coatings [12]. It has also been used to decrease the difference in reduction potential between two different metals and to avoid Fe(OH) 2 precipitation due to the high hydroxide concentration of the ZnFe alloy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what was proposed by Ravindran Further increase of concentration of TEA caused the disappearances of second and third anodic peaks during zinc-nickel alloy electrodeposition from sulfamate bath. 15 The results indicate the addition of TEA can avoid the formation of Cu(OH) 2 on the surface of copper anode and ensure the continuous dissolution of the anode. By measuring the weight loss of copper anode, it was found that under the same amount of quantity of electric charge (1 A · h), the copper weight loss with a solution containing 0.114 M TEA was 5.9% higher than that without TEA.…”
Section: Resultsmentioning
confidence: 93%